PENGARUH PEMBERIAN AIR KELAPA MUDA TERHADAP PENURUNAN TEKANAN DARAH TINGGI PADA IBU HAMIL - Novita Br Ginting Munthe; G.F Gustina Siregar; Rizka Wulandari; Iskandar Markus Sembiring; Basyariah Lubis (JURNAL KESMAS DAN GIZI (JKG), 2021)
Hypertension of pregnancy is one of the causes of morbidity and mortality worldwide for both mother and fetus. One of the treatment for high blood pressure is herbal treatment by drinking young coconut water. Young coconut water has content such as sugar, protein, potassium, calcium, magnesium, vitamin C. The high potassium content in young coconut can lower blood pressure, so young coconut water can be used to lower blood pressure. The purpose of this study was to determine the effect of giving young coconut water on blood pressure in pregnant women at Nining Pelawati Pratama Clinic, Deli Serdang Regency. The method used in this study is quantitative research using a Quasy Experiment research design with a pre test and post test design with a sample of 20 respondents. The study was conducted using the Wilcoxon test, it was found that 90% of respondents who had been given young coconut water experienced a decrease in high blood pressure and 10% of respondents did not experience a change in high blood pressure. The results of the analysis showed that the p value for systolic and diastolic respondents was 0.001 (p < 0.05) which indicated that there was an effect of giving young coconut water to blood pressure in patients with high blood pressure. It can be concluded that young coconut water can reduce systolic and diastolic blood pressure in patients with high blood pressure.